Odpowiedź:
x-3y-2 = 0
-3y= -x +2 /(-3)
y = x /3 - 2/3
dla równoległej a = 1/3
przechodzi przez P (-2;4)
y = ax +b
4 = 1/3 ·(-2) + b
b = 4 + 2/3
równanie równoległej y = 1/3 x + 4i2/3
-- ----
równanie prostopadłej
a = - 1/ (1/3)
a = -3
przechodzi prze P (-2,4)
4 = -3 · (-2) + b
b = -2
równanie prostopadłej
y = -3x -2
----------
zad b)
3x -y +3 = 0
y = 3x +3
dla równoległej a
a = 3
punkt P ( 5;-2)
y = ax +b
-2 = 3·5 + b
b = -2 -15
b = - 17
równanie równoległej
y = 3x - 17
prostopadła
a = - 1/3 punkt P (5;-2)
y= ax +b
-2 = -1/3 · 5 + b
b = -2 + 5/3
b = - 1/3
równanie prostopadłej
y = - 1/3 x - 1/3
Szczegółowe wyjaśnienie: